ChemInform Abstract: Catalysis by Dendrimer‐stabilized and Dendrimer‐encapsulated Late‐transition‐metal Nanoparticles. Issue 38 (30th August 2013) - Astruc, Didier; Diallo, Abdou; Ornelas, Caria
Abstract Review: 158 refs.